Seasonal Incidence of Eclampsia amongst Pregnant Women: Our experience at a tertiary care hospital - Naheed Akhter, Madiha Iqbal, Sana Iqbal, Shandana Khan, Sabah Safdar, Basharat Ahmad, (Pakistan Journal of Medical & Health Sciences, 2023)
Background: The causes of preeclampsia and eclampsia, two serious maternal disorders, are unknown. Understanding the precise correlation between various weather patterns may aid us in determining the possible causes of these phenomena. Eclampsia is associated with decreased temperature, increased humidity, and decreased barometric pressure. Aim: To understand the correlation between weather changes and the prevalence of eclampsia in patients visiting Khyber Teaching Hospital Peshawar. Methods: This cross sectional study was carried out at Department of Gynaecology and Obstetrics Khyber Teaching Hospital Peshawar from July 2020 to June 2021. We conducted a retrospective analysis of data collected over a 12-month period, noting the prevalence of eclampsia in our patients who presented for delivery. Results: Total 5330 deliveries over a 12-months period wererecorded. Age ranged between 16-45 years with a mean age of 30.5 years. Total 2110(39.6%) belong to maternal age of 16-20 years, 2280(42.8%) in 21-30 years and 940(17.6%) belongs to maternal age of 31-45 years. The highest number ofdeliveriesoccurredinsummer 1720(32.2%), followed by 1412(26.5%) in winter, 1190(22.3%) in Spring and 1008(18.9%) in Fall season. Practical implication: The result of this study is important for improving the quality-of-life and survival status of mothers and newborn babies and for social-capital and sustainable economic growth of the country at large. Conclusion: A slight reduction in the incidence of eclampsia was related with delivering in the fall as opposed to the winter. This is because the incidence of eclampsia has a direct linear association with rising temperature. Keywords: Eclampsia, Weather, Climate, Temperature, Humidity, Atmospheric pressure.